Composição química e degradabilidade ruminal de silagens da cana-de-açúcar tratada com aditivos químicos e bacteriano1 - De Souza Fortaleza, Ana Paula; Da Silva, Leandro Das Dores Ferreira; Zackm, Edward; Barbero, Rondineli Pavezzi [UNESP]; De Azambuja Ribeiro, Edson Luis; Pegoraro, Mauricius; Dos Santos, Luiz Eduardo; Mizubuti, Ivone Yurika (Universidade Estadual de Londrina, 2012)
The objective of this trial was to evaluate the effect of the addition of chemical and bacterial additive in the ensiling of sugar cane (Saccharum officinarum L.) on chemical composition, pH, kinectic fraction and in situ degradation of nutritions components of silages. Five rumen-cannulated 1/2 Simental + 1/2 Zebu steers were allotted to a completely randomized design. The steers were placed in individual cages and they were fed with diets with 76% forage (%DM). Five silages were evaluated: control - sugar cane, no additives; urea - sugar cane + 0.5% of urea (wet basis); inoculant - sugar cane inoculated with LactoSilo® (390 g/40 t forage); NaOH - sugar cane + 1.0% of sodium hydroxide (wet basis); CaOH - sugar cane + 0.6% of calcium hydroxide (wet basis). The silage additives with sodium hydroxide showed the highest pH values before (11.20) and after (4.87) for silage. No differences were observed among the silages for dry matter (26.85), crude protein (5.25) and acid detergent fiber (57.21). Fractionation of dry matter and organic matter of silages showed similar behavior, with higher values of the soluble fraction (fraction A) for silages with sodium hydroxide (45.86 and 30.95%) and calcium hydroxide (29.47 and 26.13%). The use of sodium hydroxide allowed obtaining higher values for the degradation of cell wall components of silages from cane sugar. The potencial and effective degradability with 3, 5 and 8%/h of passage rate were respectively 88.44, 64.45, 56.73 and 49.83% for NDF and 82.57, 55.51, 46.72 and 38.83% for ADF, indicating that the use of sodium hydroxide as chemical additives can improve the nutritive value of cane sugar silage.
Chemical composition and ruminal degradability of the sugar cane silage treated with chemical and bacterial additives
Keywords: Calcium hydroxide; Ruminal kinetics; Sodium hydroxide; Urea